A new brachycladiid species (Digenea) from Gervais' beaked whale Mesoplodon europaeus in north-western Atlantic waters - Fraija-Fernández, N.; Aznar, F. J.; Raga, J. A.; Gibson, D.; Fernández, M. (Acta Parasitologica, 2014)
A new species of the digenean family Brachycladiidae Odhner, 1905 is described from the bile ducts of a Gervais’ beaked whale Mesoplodon europaeus Gervais (Ziphiidae) stranded on the North Atlantic coast of Florida. These parasites were assigned to Brachycladium Looss, 1899 and differed from other species of the genus in the relative size of the oral and ventral suckers, the form and size of the eggs and their extremely small body size. A canonical discriminant analysis was used to examine differences between these specimens and the smallest available individuals of B. atlanticum (Abril, Balbuena and Raga, 1991) Gibson, 2005, considered the morphologically closest species. The overall results exhibited significant differences between the two samples and a jack-knife classification showed that 96.2% of the specimens were correctly classified to their group. In view of evidence from morphological data, the specimens from M. europaeus are considered as new to science and are designated as Brachycladium parvulum n. sp.